Proceedings of 36th International Cosmic Ray Conference — PoS(ICRC2019) 2019
DOI: 10.22323/1.358.0933
|View full text |Cite
|
Sign up to set email alerts
|

Arrival direction reconstruction of ultra-high-energy neutrinos with ARA

Abstract: Askaryan Radio Array (ARA) deploys antennas in the Antarctic ice with a 3D lattice shape, looking for Askaryan emission produced by interactions of high-energy neutrinos. Currently, the construction of the detector is ongoing, and five independent stations have been deployed. Two types of antennas are used to measure the polarization of the radio wave produced by neutrino-induced showers. Each antenna is designed to be sensitive to a vertically or horizontally-polarized radio wave. The polarization information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The signal arrival direction can be determined to sub-degree precision via the signal arrival times to the different antennas of a detector station [199,208,209]. The index-ofrefraction profile is known well enough to achieve sub-degree precision on the signal direction, as tested in measurements at the South Pole [208].…”
Section: Reconstruction Of Energy and Directionmentioning
confidence: 99%
“…The signal arrival direction can be determined to sub-degree precision via the signal arrival times to the different antennas of a detector station [199,208,209]. The index-ofrefraction profile is known well enough to achieve sub-degree precision on the signal direction, as tested in measurements at the South Pole [208].…”
Section: Reconstruction Of Energy and Directionmentioning
confidence: 99%
“…In previous studies we have shown that polarization is the dominant uncertainty on the neutrino direction [7,12,13]. The other parameters that impact the neutrino direction, namely signal arrival direction [20] and viewing angle, can typically be measured more precisely. Thus, an accurate reconstruction of signal polarization is the key to improve reconstructed neutrino angular resolution.…”
Section: Jcap04(2022)022mentioning
confidence: 99%
“…The signal arrival direction can be determined to subdegree precision via the signal arrival times to the different antennas of a detector station [199,208,209]. The index-of-refraction profile is known well enough to achieve sub-degree precision on the signal direction, as tested in measurements at the South Pole [208].…”
Section: Reconstruction Of Energy and Directionmentioning
confidence: 99%